Changes in the quantitative characteristics of the Ukrainian market of tear replacement products for dry eye disease over 2016-2019 - V. M. Sakovych; Yu. O. Tomashevska; O. V. Makarenko; O. V. Kryvoviaz; M. S. Garnyk (Ukrainian Society of Ophthalmologists, 2022)
Background: Management of dry eye syndrome (DES) is a current medical, pharmaceutical and social issue both globally and in Ukraine. Purpose: To assess changes in quantitative characteristics of the Ukrainian market of tear replacement products (TRPs) for dry eye disease over 2016-2019. Material and Methods: Data from the national pharmacy-related registers and from PharmXplorer, a marketing research database from Proxima Research LLC, were used for research. Sales were assessed in terms of both packages and Ukrainian hryvnias (₴). Retrospective, structural and graphical methods were used for research. Results: Of the TRPs available on the market, only 10.7% were Ukrainian products. Almost half (46.43%) of the TRPs were those whose price range was from ₴101 to ₴200. The smallest share of the market (14.28%) was attributed to the most expensive TRPs. In addition, almost half of the products of the lowest price range (₴100 and under) were domestic products. Conclusion: the number of domestic TRPs in the Ukrainian pharmaceutical market is limited. A stable increase in TRP retail sales both in packages and hryvnias indicates a stable and positive increase in demand for therapeutic products for dry eye patients. A Ukrainian lowest-price niche medical device containing both dexpanthenol and taurin was an absolute leader of 2016-2019 TRP retail sales.